Analysis of Chemical Properties and Heavy Metals from Cisadane River, Tangerang, Indonesia - Desy Rosarina; Ellysa Kusuma Laksanawati; Dewi Rosanti (Universitas Diponegoro, 2021)
This paper explained heavy metals and chemical properties from the Cisadane River in Tangerang City. A survey method was used to determine the place for sampling the test material. Water measurement is carried out in situ and laboratory tests. Data retrieval was done by purposive sampling determining three observation stations, namely in the Taman Gajah Tunggal park area (station1), Babakan Cikokol residential area (station 2), and Karawaci paper mill area (station 3). The analysis was carried out exactly using analysis. Namely, analysis carried out in the laboratory. The parameters observed were COD, phosphate, DO, BOD, pH. Results of this study informed the water quality in the Cisadane City river did not meet Class II Water Quality Standards based on Government Regulation Number 82, the year 2001. The COD content only meets class II water quality standards at stations 1 and 3. BOD and phosphate content is high and exceeds class II water quality standards. Heavy metal content still meets the water quality standard threshold with a value of Cd less than 0.01 mg/L, Cu less than 0.02 mg/L, Pb less than 0.03mg/L, and Cr less than 0.05mg/L. Zn content exceeds the water quality standard threshold at station three and meets water quality standards at stations 1 and 2 with a value of less than 0.05mg/L.